Testing The Laxative Activity of Utasupe Leaf Juice from The Ende Region on White Rats (Rattus novergicus) Loperamid Induced Constipation Model - Hendrik, Einstein Daud Victor; Nurina, Rr. Listyawati; Manafe, Derri Tallo; Rini, Desi Indria; Dean, Muhajirin (Jurnal Biologi Tropis, 2026)
Constipation is a problem in the pattern of elimination due to the presence of dry or hard feces passing through the large intestine, while a laxative is a substance that can provide stimulation of intestinal peristalsis as a reflex of direct stimulation of the intestinal wall that can facilitate defecation. Many medicinal plants can treat constipation, one of which is Utasupe. Utasupe is a vegetable plant originating from the Ende region. In Ende, Utasupe is believed to facilitate bowel movements, so people often consume Utasupe. This study aims to determine the laxative effect of Utasupe leaf juice from Ende region on loperamide-induced male white rats (Rattus novergicus). The study was conducted experimentally on 30 Sprague daley strain white rats aged 8-12 weeks. The parameter for testing the laxative effect was the defecation pattern, while the observed parameter was the frequency of defecation every hour for 8 hours. Utasupe leaf juice was administered orally at a dose of 125 mg/mL, 250 mg/mL and 500 mg/mL, as a comparison negative control (Na-CMC) and positive control (Bisacodyl) were used. The results showed that the administration of Utasupe leaf juice at a dose of 250 mg/mL had a laxative effect on male white rats. Utasupe leaf juice has laxative activity in white rats (Rattus novergicus). The time required for defecation to occur after being given Utasupe leaf juice from the Ende area in white rats (Rattus novergicus) is one hour with the most effective dose is 250 mg/mL.